Economic analysis of corruption at the company level - Paulina Bąk (Central European Economic Journal (CEEJ), 2020)
Corruption is a factor that affects a company severely either directly or indirectly. It may have a positive or negative impact on the economic situation of the company. This article verifies the hypothesis about the corporate perception of corruption as an obstacle to business performance. It also identifies which factors do have a substantial effect on the perception of corruption by companies. The study was carried out using the logit model. The data used were obtained from the Business Environment and Enterprise Performance Survey (BEEPS) database for 2016.
Keywords: G34; G38; 330; corruption; companies; extortion